Ginsenoside Rb1 Modulates the Migration of Bone-Derived Mesenchymal Stem Cells through the SDF-1/CXCR4 Axis and PI3K/Akt Pathway. (10th March 2022) - Liu, Yimei; Liu, Ninghua; Li, Xiangyang; Luo, Zhe; Zhang, Jing
Abstract : Background and Objectives . Bone mesenchymal stem cells (BMSCs) play a vital role in skin wound healing and skin regeneration through proliferation, migration, and paracrine interactions. A previous study indicated that ginsenoside Rb1 acted as a vital antidotal component which antagonized the oxidative stem cell. However, the effect and mechanism of ginsenoside Rb1-mediated BMSC migration remained unknown. Methods . Wound-healing assay and Transwell assay were utilized to evaluate the effect of ginsenoside Rb1 on the migration of BMSCs. RT-PCR and Western blotting were performed to evaluate the expression of stromal-derived factor 1 (SDF-1), C-X-C chemokine receptor type 4 (CXCR4), phosphatidylinositol 3-kinase (PI3K), and protein kinase B (PKB; AKT). Results . Ginsenoside Rb1 significantly enhanced the migration of BMSCs through the activation of SDF-1, CXCR4, p-PI3K/PI3K, and p-Akt/Akt relative expression. Furthermore, this stimulus was blocked by the pretreatment with AMD3100 and LY294002. Conclusions . Ginsenoside Rb1 facilitated the migration of BMSCs through the activation of the SDF-1/CXCR4 axis and PI3K/Akt pathway.